PRUKADES (FEATURED PRODUCT OF RURAL AREA) IN INCREASING HOME INDUSTRY PRODUCTIVITY IN PAMEKASAN - Ahmad Rajaul Masrur; Hajjatul Mabbruroh; Darwis Darwis (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2019)
Low productivity in home industry which produces featured product in rural area in Pamekasan cannot cover entire market target nationally or internationally. Featured Product of Rural Area (PRUKADes) is the first program of 4 priority planned by Ministry of Village, Disadvantaged Regions and Trasmigration (Kemendes PDTT) aims to increase village competitiveness and company’s productivity in order the villagers gain higher income. Based on the statistic analytical test, a result is valid if r is bigger than r in table. In addition, data is considered reliable because the value of Cronbach's Alpha is 0,77 or more than 0,6. From double linear regression analysis, the value is 0,800. It shows that there is a strong relationship between home industry productivity (X) through X1 (workers quality), X2 (managing skill), and X3 (Input and Output process) and the increasing featured product of rural area in Pamekasan (Y). The value is 64,0% and it is quite big. The rest is 36,0% and it is influenced by other factors that excluded from this research. Entirely, the research is done by F test F (ensemble regressed coefficient); that is, there is a relationship between home industry productivity (X) and the increase of featured product in rural area in Pamekasan (Y